The STRUT vowel in urban and rural accents of the West Midlands - Łodzikowski, Kacper; Malarski, Kamil (My University, 2012)
This pilot study investigates the speech of three West Midlands communities: a city (Birmingham), a town (Stratford-upon-Avon) and two villages (Alderminster and Wimpstone). We focus on the STRUT vowel, an important criterion for separating the linguistic South from the linguistic North (Wells 1982: 349). We provide more evidence for the phonemic distinction between /ʊ/ and /ʌ/ in the West Midlands, and show that phonetically the STRUT vowel is neither typically northern nor southern. Through vowel instrumental analysis, we establish to what extent the southern innovation of the STRUT vowel has been developed in each community.
Keywords: sociophonetics; accents of English; West Midlands accent; STRUT vowel